Plasmodium falciparum rosetting protects schizonts against artemisinin - Lee, Wenn-Chyau (2022)
Background: Artemisinin (ART) resistance in Plasmodium falciparum is thought to occur during the early stage of the parasite's erythrocytic cycle. Here, we identify a novel factor associated with the late stage parasite development that contributes to ART resistance. Methods: Rosetting rates of clinical isolates pre- and post- brief (one hour) exposure to artesunate (AS, an ART derivative) were evaluated. The effects of AS-mediated rosetting on the post-AS-exposed parasite's replication and survival, as well as the extent of protection by AS-mediated rosetting on different parasite stages were investigated. The rosetting ligands, mechanisms, and gene mutations involved were studied. Findings: Brief AS exposure stimulated rosetting, with AS-resistant isolates forming more rosettes in a more rapid manner. AS-mediated rosetting enabled infected erythrocytes (IRBC) to withstand AS exposure for several hours and protected the IRBC from phagocytosis. When their rosetting ability was blocked experimentally, the post-AS exposure survival advantage by the AS-resistant parasites was abrogated. Deletions in two genes coding for PfEMP1 exon 2 (PF3D7_0200300 and PF3D7_0223300) were found to be associated with AS-mediated rosetting, and these mutations were significantly selected through time in the parasite population under study, along with the K13 mutations, a molecular marker of ART-resistance. Interpretation: Rapid ART parasite clearance is driven by the direct oxidative damages on IRBC by ART and the phagocytic destruction of the damaged IRBC. Rosetting serves as a rapid ‘buying time’ strategy that allows more parasites to complete schizont maturation, reinvasion and subsequent development into the intrinsically less ART-susceptible ring stage.